THE 5 STRATEGY TO ENHANCE INDONESIAâS AGRO-BASED INDUSTRY COMPETITIVENESS - Joewono, Handito Hadi (Journal of Indonesian Economy and Business, 2008)
Within the period of 1995-2000, the international competitiveness of Indonesia agrobasedindustry sector had declined, down under the position of Thailand and China which areused as benchmark in this study. The decreasing of Indonesia domestic competitivenesswithin the same periode of time was more frustrated. This study was also find the linkage ofIndonesia agro-based industry sector to Thailand and China.This study had an objective to analyse the competitiveness position of agro-basedindustry sector in Indonesia by analysing input-output in some Asiaâs countries, especiallybetween Indonesia, Thailand, and China. Specifically, the purpose of this study are : (1)Measuring the change of agro-based industry competitiveness in Indonesia, Thailand, andChina; (2) Analysing the linkage between agro-based industry sector in Indonesia with theeconomy of Thailand and China; and (3) Calculating and analysing structural growth factorsof agro-based industry sector in Indonesia, Thailand, and China.The analysis in this study used multilateral I-O model and data from Asian I-O Table1995 and 2000 to get the competitiveness score through IIC (Index of InternationalCompetitiveness) and IDC (Index of Domestic Competitiveness), inter-country linkages, keysector and sources of growth through structural decomposition.This study founds that Indonesia had no primary source of growth in agro-basedindustry that could be used in the future development. Structural growth factor in agro-basedindustry sector in Indonesia did not have a pattern, while Thailand was supported bytechnological change factor, and China was supported by export expansion factor.Based on the above findings, this study come to some recommendations to increaseIndonesia agro-based industry competitiveness as follows : (1) Developing agro-basedindustry as a key economic sector, (2) Increasing productivity, (3) Strengthening domesticcompetitiveness, (4) Increasing marketing-based competitiveness, (5) Developing technologybasedeconomy.Keywords: competitiveness, linkages, sources of growth, agro-based industry